1999
DOI: 10.1161/01.res.85.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Cell Cycle Proteins and Prolonged Duration of Cardiac Myocyte Hyperplasia in p27 KIP1 Knockout Mice

Abstract: Abstract-The precise role of cell cycle-dependent molecules in controlling the switch from cardiac myocyte hyperplasia to hypertrophy remains to be determined. We report that loss of p27 KIP1 in the mouse results in a significant increase in heart size and in the total number of cardiac myocytes. In comparison to p27 KIP1 ϩ/ϩ myocytes, the percentage of neonatal p27 KIP1 Ϫ/Ϫ myocytes in S phase was increased significantly, concomitant with a significant decrease in the percentage of G 0 /G 1 cells. The express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 48 publications
2
66
0
Order By: Relevance
“…Transgenic mice over-expressing c-myc in the heart displayed mild developmental hyperplasia but cardiac myocytes eventually ceased cell division (Jackson et al 1991). Similarly, p27 null mice also demonstrated an increased number of cardiac myocytes in the adult mouse heart suggesting that this molecule acts as part of the timing mechanism that controls myocyte cell cycle exit (Poolman et al 1999). Other recent studies from our laboratory have shown that over-expression of cyclin B1 in neonatal cardiac myocytes extends the proliferative potential of these cells (Bicknell & Brooks 2002b).…”
Section: Targeting the Cell Cycle Machinery In Cardiovascular Cellsmentioning
confidence: 99%
“…Transgenic mice over-expressing c-myc in the heart displayed mild developmental hyperplasia but cardiac myocytes eventually ceased cell division (Jackson et al 1991). Similarly, p27 null mice also demonstrated an increased number of cardiac myocytes in the adult mouse heart suggesting that this molecule acts as part of the timing mechanism that controls myocyte cell cycle exit (Poolman et al 1999). Other recent studies from our laboratory have shown that over-expression of cyclin B1 in neonatal cardiac myocytes extends the proliferative potential of these cells (Bicknell & Brooks 2002b).…”
Section: Targeting the Cell Cycle Machinery In Cardiovascular Cellsmentioning
confidence: 99%
“…This is caused by the lack of G1 cyclin/cyclin-dependent kinases (Cdk), crucial positive cell-cycle modulators, and high levels of cell-cycle inhibitors (8), such as the retinoblastoma proteins pRb/p130 (9) and the Cdk inhibitors (Cdki) p21/p27 (10). The limited mitotic capacity of mature CM (11) renders the adult mammalian heart functionally unable to repair itself after ischemic injury (12).…”
mentioning
confidence: 99%
“…These mice have multi-organ enlargement that includes the heart where there is prolonged proliferation of cardiac myocytes and a perturbation of cardiac myocyte hypertrophy (45). These data again underscore the possibility that specific targeting of certain cell regulatory molecules will enable the initiation of cell division in healthy cardiac myocyte that surround an injured area.…”
Section: Myocardial Infarctionmentioning
confidence: 78%